2013
DOI: 10.5194/angeo-31-787-2013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the characteristics of ionospheric parameters obtained from FORMOSAT-3 and digisonde over Ascension Island

Abstract: Electron density profile data obtained from the FORMOSAT-3 radio occultation (RO) measurements over Ascension Island are used to study the bottomside thickness parameter B0 in the International Reference Ionosphere (IRI) model, scale height around the F region peak height, and other F2 region parameters. The RO data were collected when the radio occultation occurred at Ascension Island (345.6° E, 8.0° S) during the solar minimum activity period from May 2006 to April 2008. Results show that the B0 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
1
24
2
Order By: Relevance
“…For example, Krankowski et al [] obtained a correlation ( R ) of 0.986 when validating COSMIC N m F 2 with ionosonde data over European midlatitude region during 2008, while R values of 0.96 [ Chu et al , ] and 0.92 [ Habarulema et al , ] were reported for global and African sector studies using 2006 and 2008 data, respectively. Furthermore, single station [e.g., Chuo et al , ] and global simulation [e.g., Yue et al , ] studies have also reported R values (0.96 and 0.95) in the same range. Comparing GPS/MET‐derived N m F 2 with collocated ionosonde observations, Hajj and Romans [] reported an agreement to within 20% at 1 σ level.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Krankowski et al [] obtained a correlation ( R ) of 0.986 when validating COSMIC N m F 2 with ionosonde data over European midlatitude region during 2008, while R values of 0.96 [ Chu et al , ] and 0.92 [ Habarulema et al , ] were reported for global and African sector studies using 2006 and 2008 data, respectively. Furthermore, single station [e.g., Chuo et al , ] and global simulation [e.g., Yue et al , ] studies have also reported R values (0.96 and 0.95) in the same range. Comparing GPS/MET‐derived N m F 2 with collocated ionosonde observations, Hajj and Romans [] reported an agreement to within 20% at 1 σ level.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, some comparative studies between RO and ground‐based observations preferred analyses during geomagnetically quiet conditions [e.g., Chu et al , ; Wu et al , ] to avoid errors related to the occurrence of ionospheric electron density irregularities. However, other studies have done validation case studies on one storm period [e.g., Krankowski et al , ], while significant literature that exists performs statistics based on large data sets without necessarily doing any isolation based on geomagnetic activity or occurrence of ionospheric irregularities [e.g., Yue et al , ; Chuo et al , ; Pedatella et al , , and references therein]. These studies give an indication that RO data may be able to follow ionospheric dynamics even during geomagnetic storms, although not in a detailed quantitative sense.…”
Section: Introductionmentioning
confidence: 99%
“…Chuo et al, 2011). Comparison of characteristics of ionospheric parameters obtained from COSMIC and a digisonde over Ascension Island also illustrates similar diurnal variation and high correlation for both NmF2 (> 0.91) and hmF2 (> 0.72) in the equinox, summer and winter periods (Chuo et al, 2013). Comparison between RO EDPs from the COSMIC satellites with digisonde data over the Brazilian region shows generally good correlation for NmF2 (0.92) and hmF2 (0.78) (Ely et al, 2012).…”
Section: Discussionmentioning
confidence: 61%
“…Statistical comparisons of ionospheric peak parameters (NmF2 and hmF2) measured by COSMIC satellites and ionosondes indicate that there are considerable high correlations between COS-MIC and ionosonde ionospheric parameters (Lei et al, 2007;Chu et al, 2010;Chuo et al, 2011Chuo et al, , 2013Ely et al, 2012;Krankowski et al, 2011;J.-Y. Liu et al, 2010;Hu et al, 2014).…”
Section: Hu Et Al: Validation Of Cosmic Ionospheric Peak Parametersmentioning
confidence: 99%
“…The impacts of the recent deep and prolonged solar minimum on the electron density, temperature, spread F, and total electron content, as well as the vertical and zonal plasma drifts, over the equatorial and low-latitude ionosphere have been studied using different types of observational data, such as digisondes (Liu Libo et al, 2011;Candido et al, 2011;Chuo et al, 2013;Solomon et al, 2013;Narayanan et al, 2014), satellites (Solomon et al, 2011;Huang et al, 2010Huang et al, , 2012Chuo et al, 2013;Fejer et al, 2013) and incoherent scatter radar (Aponte et al, 2013;Kotov et al, 2015;Santos et al, 2016a). During the period of June 2008 the mean monthly F10.7 radio index reached an extremely low value of ∼ 65.7 × 10 −22 W m −2 Hz −1 , which represented a solar extreme ultraviolet (EUV) irradiance that was lower than during previous solar cycles.…”
Section: Introductionmentioning
confidence: 99%